The Predictive Factors of Job Performance in Nurses\' Moral Distress - Yahya Zarei Nodee; Mohammad Reza Sheikhi; Zahra HosseinKhani; Mohammad Ali Soleimani (Hamadan University of Medical Sciences, 2021)
Background: Moral distress is one of the most complex ethical problems for nurses working in Intensive Care Units. Desired job performance of the nurse guarantees the quality of health care provided to patients and is an important factor in accelerating the process of treatment and recovery of patients. This study was conducted to investigate the predictive factors of job performance in nurses' moral distress. Materials and Methods: This is a descriptive cross-sectional study, in which 256 nurses working in ICU wards of private and public hospitals of Qazvin province (from January to March 2019) were selected through convenience sampling method. Demographic characteristics questionnaire, Six Dimension Scale of Nursing Performance and Modified Moral Distress Scale-Revised were used for data collection. Statistical analysis was performed using linear regression model test in SPSS 22. Results: The results showed that the mean score of nurses' moral distress was 171.37±55.63. In the multivariate linear regression model, only educational dimension of job performance in both frequency (β=-26.37, P=0.001) and quality (β =-76.15, P=0.025) correlated significantly with moral distress. Conclusion: Based on the results of the present study, the educational dimension of job performance is a predictive factor for moral distress. Therefore, steps can be taken to reduce moral distress in clinical settings, such as the use of nurses with specialized training in Intensive Care Units, paying special attention to teaching ethical issues in nursing centers and holding retraining courses for nurses.